2022
DOI: 10.1111/jfbc.14075
|View full text |Cite
|
Sign up to set email alerts
|

Armillaria mellea fermentation liquor ameliorates p‐chlorophenylalanine‐induced insomnia associated with the modulation of serotonergic system and gut microbiota in rats

Abstract: In China, Armillaria mellea (Vahl) P. Kumm. has been used as a folk medicine to treat insomnia for several hundred years. However, the underlying mechanisms involved are currently unknown. In this study, the anti-insomnia efficacy of A. mellea fermentation liquor (AFL) was evaluated in p-chlorophenylalanine-induced insomnia rats by measuring the serotonergic systems and gut microbiota. Our results demonstrate that all doses of AFL significantly reduced locomotor activity and alleviated decreasing weights in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In previous studies, propionate induced the gene transcription of tyrosine hydroxylase, an enzyme involved in catecholamine biosynthesis ( Nankova et al, 2014 ; Dalile et al, 2019 ), which acts as a neurotransmitter in the center neuron system. Yao et al (2022) and Si et al (2022a) demonstrated a relationship between PCPA administration and dysbiosis in animals. Especially, the latter study showed that PCPA-induced 5-HT depletion affects gut microbiota in rodents.…”
Section: Introductionmentioning
confidence: 98%
“…In previous studies, propionate induced the gene transcription of tyrosine hydroxylase, an enzyme involved in catecholamine biosynthesis ( Nankova et al, 2014 ; Dalile et al, 2019 ), which acts as a neurotransmitter in the center neuron system. Yao et al (2022) and Si et al (2022a) demonstrated a relationship between PCPA administration and dysbiosis in animals. Especially, the latter study showed that PCPA-induced 5-HT depletion affects gut microbiota in rodents.…”
Section: Introductionmentioning
confidence: 98%
“…Discrepancies in findings between our study and others may be attributed to species-specific differences and methodological variations. 48 In conclusion, the experimental results affirm the potential of AM in alleviating insomnia by modulating serotonergic systems and gut microbiota. As a popular edible and medicinal mushroom, AM also holds promise for the future development and production of innovative food products.…”
Section: Insomnia Prevention Activitiesmentioning
confidence: 54%
“…Discrepancies in findings between our study and others may be attributed to species-specific differences and methodological variations. 48…”
Section: Bioactivities Of Ammentioning
confidence: 99%
“…Compared to the normal control group, the body mass of rats in the modeling group was significantly reduced. Compared with the model control group, after 6 days of treatment with valerian volatile oil ( 33 ), the rats had a normal diet, regular circadian rhythm, and increased body mass, as shown in Figures 6A,B . These phenomena showed that valerian volatile oil had a certain effect on improving the insomnia of rats.…”
Section: Resultsmentioning
confidence: 99%